Caught between ideal and reality: A study on occupational burnout among inside-system legal professionals under the rule-of-law reform in contemporary China. (October 2017) - Bi, Xiangyang
This paper analyzes job burnout of inside-system legal professionals under the rule-of-law reform in China and its possible causes. Social cognitive theory, including cognitive dissonance, expectancy theory, and social comparison theory, provides the analytic framework for this study. The conclusion reveals a relatively high level of job burnout among inside-system legal professionals in China. Further analysis indicates that the individual's commitment to the rule of law, confidence in the legal reform, and practice of non-rule-of-law in daily work are influential factors affecting his/her job burnout levels. Importantly, the interaction coefficients between these variables are statistically significant, clearly demonstrating that the discrepancy between expectation and reality is one of the root causes of job burnout in the legal profession. The discrepancy causes cognitive dissonance and psychological imbalance. At a theoretical level, this finding opens a new way of examining a particular type of occupational burnout. It shows that under the rule-of-law reform, Chinese inside-system legal professionals exhibit cognitive dissonance between ideals and reality, which constitutes a micro-political psychological basis for organizational change as speculated by neo-institutionalists and, in turn, reveals insights that may help us to understand the legal reform process within the bureaucratic system.